Transformation of Physics Learning: A Study of the Determinants of Active Student Participation - Dedi Riyan Rizaldi; Salwa; Rabiatul Hasanah; Ahmad Yadaeni; M. Helmi Hariadi; Lalu Muliyadi; Muhammad Hanafi; Hizbul Wathoni; Ziadatul Fatimah (Lembaga Einstein College (LEC), 2026)
The aim of this study is to analyze the internal and external factors influencing student learning activeness and identify the most dominant factor among students in Class XI MIPA at MA Plus Nurul Islam. Focusing on internal factors (motivation, self-efficacy, and learning readiness), external factors (class environment, teacher support, peers, and facilities), media and teaching methods, and parental and home environment support, the research employs a quantitative descriptive approach with a case study method. Data were collected via questionnaires (Likert scale) and documentation from respondents. The results indicate that all factors positively contribute to learning activeness, with media and teaching methods achieving the highest mean score (4.12 or 82.4%), followed by external factors (3.95 or 79.0%), internal factors (3.87 or 77.4%), and parental and home support (3.72 or 74.4%). These findings emphasize the importance of interactive teaching methods and collaborative environments to enhance student engagement. Recommendations include teachers adapting methods for greater interactivity, schools improving facilities, and parents increasing academic involvement to optimize learning outcomes in senior high school physics education